Long-term effects of intrajejunal levodopa infusion on sleep in people with advanced Parkinson's disease - Diaconu, Ştefania; Irincu, Laura; Ţînţ, Diana; Falup-Pecurariu, Cristian (Frontiers in Neurology, 2023)
Background: Sleep disturbances are commonly encountered in people with advanced Parkinson’s disease (PD). In these stages, levodopa-carbidopa intestinal gel (LCIG) is recommended for improving motor symptoms, some non-motor dysfunctions, and quality of life in these patients. The aim of this study was to assess the effects of LCIG on sleep in PD in a longitudinal study. Study Design: Open-label observational study in patients with advanced PD undergoing LCIG treatment. Measures and Outcomes: Ten consecutive advanced people with PD were evaluated at baseline and after 6 months and 1 year respectively of LCIG infusion. Sleep parameters were assessed with several validated scales. We assessed the evolution of sleep parameters under LCIG infusion over time and the effects on sleep quality. Results: Significant improvement following LCIG was observed in PSQI total score (p = 0.007), SCOPA sleep total score (p = 0.008), SCOPA-NS subscale (p = 0.007) and AIS total score (p = 0.001) at 6 months and 1 year, comparing with baseline. The PSQI total score at 6 months correlated significantly with PDSS-2 “disturbed sleep” item at 6 months (p = 0.28; R = 0.688), while the PSQI total score at 12 months correlated with PDSS-2 total score at 1 year (p = 0.025, R=0.697), and with AIS total score at 1 year (p = 0.015, R = 0.739). Conclusions: LCIG infusion demonstrated beneficial effects on sleep parameters and sleep quality, which were constant over time for up to 12 months.